PENGARUH PIJAT OKSITOSIN TERHADAP PENGELUARAN ASI PADA IBU POSTPARTUM DI BPM PIPIN HERIYANTI YOGYAKARTA TAHUN 2016 - Azizah, Imroatul; Yulinda, Dwi (Media Ilmu Kesehatan, 2017)
Background: The lowest exclusive brest feeding rates in DIY is in the city of Yogyakarta. Exclusive breast feeding improves infant immunity so as to minimize the occurrence of diarrhea, constipation, fever that is caused by some allergic reactions. The success of primi maternal postpartum primi exclusive breast feeding is strongly influenced by the success of the early suckle. Massaging the hip area, or the costa until scapulla can provide a sense of comfort and relax in postpartum mothers so that will help the success of early breast feeding. Objectifive:This study aimed to analyze the relationship between oxytocin massage on primipara psotpartum to timing and volume of breast milk. Method: Research was conducted on primipara maternal postpartum which is divided into two groups. They are the control group; and the treatment group which was given the oxytocin  massaged. Breast milk volume was measured at 12 hours after the massage by using a breast pump. The analytical method used is Student T-test. The results of this study showed a significant increase in the treatment group compared to the control group at p <0.05. Results: Massage oxytocin significantly increase the volume of breast milk (p 0,000) and breast milk accelerate spending (0,012)  in comparison with the control group. Conclusion: Massage oxytocin is one of the alternatives that can be done to improve the success of exclusive breast feeding on primipara maternal postpartum.   Key Words: Oxytocin massage, postpartum, timing and volume of breast milk